Unveiling the truth of interactions between microplastics and per- and polyfluoroalkyl substances (PFASs) in wastewater treatment plants: microplastics as a carrier of PFASs and beyond - Ma, Min; Coulon, Frederic; Tang, Zhiwen; Hu, Zhiyuan; Bi, Ye; Huo, Mingxin; Song, Xin (American Chemical Society, 2025)
Microplastics (MPs) and per- and polyfluoroalkyl substances (PFASs) are ubiquitous contaminants in environments, yet their co-occurrence and interactions remain insufficiently understood. In this study, we confirmed the concurrent presence of MPs and PFASs and their distinct distribution patterns in a wastewater treatment plant (WWTP) through a comprehensive sampling and analysis effort. Significant correlations (p < 0.05) were observed between specific types of MPs and PFASs, suggesting their shared sources. Moreover, MPs were identified as carriers of PFASs, with PFAS concentration ranging between 122 and 166 ng/g, predominantly consisting of perfluorooctanoic acid (PFOA) and perfluorobutanoic acid (PFBA). The laboratory verification experiment revealed that PFASs could be leached from MPs in aqueous environments, in which commercial MPs exhibited higher leaching potential, with the highest combined concentration of perfluorooctanesulfonate (PFOS), PFOA, and PFBA reaching 10.4 ng/mL. PFOS demonstrated a desorption efficiency exceeding 120% in sorption/desorption experiments, confirming its release from the MPs themselves. These results highlighted the dual roles of MPs as both carriers and sources of PFASs. The identified contaminant profiles and correlations between MPs and PFASs across different matrices in WWTP provide valuable insights and form a basis for further research into proactive measures to effectively mitigate their environmental contamination.
Keywords: 41 Environmental Sciences; 4105 Pollution and Contamination; PFASs; co-occurrence; contaminant carrier; contaminant source; emerging contaminants; microplastics; Environmental Sciences